2017
DOI: 10.1186/s13098-017-0279-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulating fasting glucagon-like peptide-1 in surgical patients with aortic valve disease and diabetes

Abstract: BackgroundDiabetes is a risk factor for peripheral, coronary, and cerebrovascular disease. In contrast, results also indicate that patients with diabetes have reduced prevalence of aortic aneurysms, although the mechanisms remain largely unknown. We hypothesize that altered endogenous secretion of the intestinal hormone glucagon-like peptide-1 (GLP-1)—previously shown to protect from aneurysm formation, and governing many of the mechanisms thought to be involved in aneurysm formation—may provide insights into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(41 reference statements)
2
4
0
Order By: Relevance
“…In accordance with previous results [10], total F-GLP-1 (35.4 ± 3.1 vs. 19.0 ± 1.4 pmol/L p < 0.0001, Figure 3a) and active F-GLP-1 (3.4 ± 0.7 vs. 1.4 ± 0.2 pmol/L, p < 0.01, Figure 3b) were higher in the T2D group, compared with the control group. As expected, a significant correlation between active and total F-GLP-1 was detected (r = 0.5575, p < 0.01, Figure 3c).…”
Section: Increased F-glp-1 Is Associated With a Th2 Inflammatory Profile In T2d Patientssupporting
confidence: 94%
See 1 more Smart Citation
“…In accordance with previous results [10], total F-GLP-1 (35.4 ± 3.1 vs. 19.0 ± 1.4 pmol/L p < 0.0001, Figure 3a) and active F-GLP-1 (3.4 ± 0.7 vs. 1.4 ± 0.2 pmol/L, p < 0.01, Figure 3b) were higher in the T2D group, compared with the control group. As expected, a significant correlation between active and total F-GLP-1 was detected (r = 0.5575, p < 0.01, Figure 3c).…”
Section: Increased F-glp-1 Is Associated With a Th2 Inflammatory Profile In T2d Patientssupporting
confidence: 94%
“…However, the GLP-1 receptor is widely expressed, and direct effects of the peptide on vascular tissue have been demonstrated. Further, although GLP-1 secretion is stimulated by nutrient intake and fasting levels are low, increased fasting plasma GLP-1 (F-GLP-1) has been detected in T2D [10] and is implicated in higher rates of energy expenditure, fat oxidation, and cardioprotective effects [11].…”
Section: Introductionmentioning
confidence: 99%
“…As GLP-1 has been shown to regulate processes that control Sdc-1 expression [ 23 , 26 , 27 , 28 ] and as the fpGLP-1 levels were upregulated in patients with aortic valve pathology in association with T2D [ 30 ] ( Figure 3 A), we investigated the possible contribution of fpGLP-1 to the increased adventitial expression of Sdc-1 in T2D patients. The expression of GLP-1R was, as expected, detected in the adventitia, facilitating the direct effects of GLP-1 ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…The decreased activity of DPP4 in plasma is congruent with some studies, while it stands in contrast to others. Krizhanovskii et al showed increased GLP1 in plasma of patients with dilatation of the ascending aorta, which could imply a decreased DPP-4 activity, and other studies have found a decreased DPP-4 activity in the plasma of patients with chronic obstructive pulmonary disease, a disease that has been linked to AAA rupture [40][41][42]. However, Lu et al detected a significant increase in DPP-4 in plasma from patients with AAA compared with the control group [16].…”
Section: Discussionmentioning
confidence: 98%